In Search of the Horned Frog (Ceratophrys ornata) in Argentina: Complementing Field Surveys with Citizen Science - Deutsch, Camila (2017)
The Horned Frog (Ceratophrys ornata) is a threatened amphibian that occurs in the temperate grasslands of Argentina, Brazil, and Uruguay. Several populations from Argentina have apparently declined and the species has not been recorded in Uruguay and Brazil for the last 35 y. In Argentina, published occurrence data based on field surveys are scarce, representing only a few localities in the Pampean Region. Considering that C. ornata is an iconic and distinctive species, we conducted a citizen science program to obtain occurrence data as a complement to field surveys. From 2008 to 2017, we used auditory and visual methods to survey adult C. ornata at 78 localities in the Pampean Region during both spring and summer. From 2015 to 2017, we conducted the citizen science program using online surveys and direct interviews to gather records obtained in the last 10 y. The citizen science program yielded 147 records, representing a nine-fold increase from the 15 records obtained during field surveys. The species occurrence areas estimated using each approach overlapped, although the area estimated by the citizen science program was almost double the extent of the occurrence area estimated based on field surveys. Our results indicate that well-designed citizen science methods can provide a cost-effective approach to collecting occurrence data for C. ornata. This is the first amphibian citizen science program in Argentina and provides a model for future amphibian studies, especially those involving charismatic yet difficult to study species like C. ornata.